A low-power digitally programmable neural recording amplifier with selectable multiunit activity (MUA) and local field potential (LFP) recording modes. (January 2020) - Omidvar, Abolfazl; Shaterian, Mostafa
Abstract: This paper presents the design of a low-power implantable neural recording amplifier in a 0.13 μ m CMOS technology. The structure consists of a cascade of 4-stages, including instrumentation amplifier (IA), buffer, high pass filter (HPF) and programmable gain amplifier (PGA). The proposed neural amplifier can select between multiunit activity (MUA) and local field potential (LFP) recording modes. A programmable gain is available in the MUA recording mode. Eight gain states can be selected from 58.4 dB to 79.5 dB with 3-bit digital control signals. The digital control signals can be made by a digital signal processing (DSP) unit. In MUA recording mode, the bandwidth is measured from 480 Hz to 8.7 kHz. In LFP recording mode, a constant midband gain of 58.4 dB is achieved in a passband of 0.36 Hz–330 Hz. A noise efficiency factor (NEF) of 1.47 is obtained for the amplifier. Power dissipation is decreased to 1.9 μW per recording channel, by biasing the transistors in the subthreshold region. The proposed neural amplifier can be used for electrocorticography (ECoG) recording in wireless implantable devices.